Expression of developing neural transcription factors in lung carcinoid tumors. (August 2014) - Endo, Tetsuya; Yazawa, Takuya; Shishido‐Hara, Yukiko; Fujiwara, Masachika; Shimoyamada, Hiroaki; Ishii, Jun; Sato, Hanako; Tachibana, Keisei; Takei, Hidefumi; Kondo, Haruhiko; Goya, Tomoyuki; Endo, Shunsuke; et al.
<x xml:space="preserve">Abstract</x> In lung tumors, the association between carcinoids and high‐grade neuroendocrine tumors (HGNETs) is controversial. To understand the phenotypic similarities/differences between lung carcinoids and HGNETs, we comparatively investigated the expression of three kinds of developing neural transcription factors (DNTFs: BRN2, TTF1 and ASCL1) and multiple endocrine neoplasia type 1 (MEN1) as well as RB1 and P53 using 18 carcinoids and 16 HGNETs. The DNTFs were expressed in 10 of the 18 carcinoids and in all the HGNETs, while normal neuroendocrine cells, which are considered the major cell origin of lung carcinoids and small cell carcinomas, did not express DNTFs. Both the DNTF‐ and DNTF+ carcinoids contained typical and atypical carcinoids. All the DNTF‐ carcinoids examined were formed in the bronchial wall. All the MEN1‐ carcinoids examined were classified into the DNTF‐ carcinoids, while all the HGNETs expressed MEN1. This finding suggests that DNTF‐ MEN1‐ carcinoids are unlikely to be precursors of HGNETs. Although the status of RB1 and P53 between carcinoids and HGNETs were apparently different, the DNTF+ carcinoids of two male patients and one female patient revealed morphologies resembling HGNET cells and relatively high Ki67 indices. Further investigation of DNTF expression in carcinoids might provide important clues to understand the association between carcinoids and HGNETs.